The Power to Adapt: How Sense of Power Predicts Number Processing. - Scholl, Annika; Bloechle, Johannes; Sassenberg, Kai; Huber, Stefan; Moeller, Korbinian (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2019)
When people solve numerical tasks, they are able to adapt their responses to characteristics of the task. This suggests that number processing is under cognitive control. Yet, such prior research on cognitive control in numerical cognition largely focused on the role of task stimuli-neglecting the role of predictors that are not directly linked to cognitive and numerical capacities. Do people who sense control in other domains (such as their interpersonal relationships) employ cognitive control differently when processing numbers? As a first step to examine this, we investigated how a person's sense of power (as a predictor known to facilitate cognitive control in other domains) predicts number processing. People sensing relatively high (rather than low) power in their everyday lives usually exert more cognitive control, which enables them to better adapt to a given task setting. Building upon this, we predicted that sense of power facilitates number processing-but, only when the task setting provides valid decision-relevant information that people can adapt to. As indicator of adaptation to the task setting, we assessed the unit-decade compatibility effect. Indeed, sense of power predicted a smaller compatibility effect (better adaptation) when valid information was available; in contrast, sense of power tended to predict a larger compatibility effect when only ambiguous information was available. These findings highlight that cognitive control in number processing not only depends on stimuli, but can also depend on broader individual factors, such as people's sensed control in interpersonal situations.